Influence of local potential plant biodiversity as green manure on soil total N, N uptake, and chlorophyll content of rice plants - SUNTORO SUNTORO; GANJAR HERDIANSYAH; HERY WIDIJANTO; HAIKAL RAFI WARDHANA; AZHAR DIMAS TJAHJANTO; CHELYNA PUSPITASARI; EKO AMIADJI JULIANTO; MAROETO MAROETO (Society for Indonesian Biodiversity, 2024)
Abstract. Suntoro S, Herdiansyah G, Widijanto H, Wardhana HR, Tjahjanto AD, Puspitasari C, Julianto EA, Maroeto. 2024. Influence of local potential plant biodiversity as green manure on soil total N, N uptake, and chlorophyll content of rice plants. Biodiversitas 25: 1655-1662. Continuous use of chemical fertilizers in the agricultural sector causes several problems. One of several solutions that can be offered is using green manure, which could restore soil fertility and be way more sustainable for the environment. A few criteria for plants to be made into green manure are having a fast decomposition process and a low C/N ratio. This research aims to discover local potential green manure based on nutrient content and response to rice plants' soil total N, N uptake, and chlorophyll content. This research used the experiment method with a single factor Randomized Completely Block Design. There were 10 treatments with 3 replications, namely P0: control; P1: NPK 200 kg/ha; P2: Rice straw 10 tons/ha; P3: Chromolaena 10 tons/ha; P4: Ipomoea 10 tons/ha; P5: Eichhornia 10 tons/ha; P6: NPK 100 kg/ha + Rice straw 5 tons/ha; P7: NPK 100 kg/ha + Chromolaena 5 tons/ha; P8: NPK 100 kg/ha + Ipomoea 5 tons/ha; P9: NPK 100 kg/ha + Eichhornia 5 tons/ha. The results showed that Chromolaena, Ipomoea, and Eichhornia have the potential to be developed as green manure because they have high N nutrient content and low C/N ratio. These three green manures can balance the NPK fertilizer and significantly increase soil total-N content, N uptake, and chlorophyll levels in rice plants. They also provide N nutrients, N uptake, and chlorophyll levels in rice plants.